Anadolu demir çağları/Anatolian Iron Ages. 24-27 Nisan 1984 tarihleri arasında İzmir'de yapılan "I. Anadolu Demir Çağları Sempozyumu"na sunulan bildiriler (1987)
Papers presented to the "I. Anatolian Iron Ages Symposium", held in Izmir during 24th-27th April 1984